Tabayyun dalam Bermedia Sosial; Studi atas Qs. al-Hujurāt (49): 6 dalam Perspektif Ma’nā cum Maghzā Sahiron Syamsuddin - Anshori, Anshori (Program Studi Ilmu Al-Qur`an dan Tafsir, Fakultas Ushuluddin, UIN Sunan Kudus, 2022)
Tabayyun in Social Media; Study on Qs. al-Hujurat (49): 6 in the Perspective of Ma'nā cum Maghzā of Sahiron Syamsuddin. The spread of fake news is now very easy to find, especially on social media, so clarification is needed as a means of filtering the information obtained. In Islam, the word clarification is termed tabayyun. This paper aims to examine the meaning of the word tabayyun in QS. al-Hujurāt (49): 6, using the Ma'na Cum Maghza approach. Three stages must be passed in this approach. First, tracing the historical meaning, concerning the meaning of the verse in classical Islam. Second, the historical phenomenal significance is looking for the meaning of the verses of the Qur'an, both in terms of intertextuality and intratextuality. Third, the dynamic phenomenal significance or the main message. This research shows the meaning of QS. al-Hujurāt (49): 6 regarding tabayyun, refers to three main messages. First, it should be noted that any information obtained is not necessarily taken for granted. Second, it is necessary to know in advance the origin of the informant by tracing it first. The third, relates to the implications, namely the clarity of the source of information and the origin of the informant, as anticipation so as not to cause problems.